Students' Problem-Solving Abilities in Solving the PISA Test in Terms of Learning Style - Sri Indah Dwirahmasari Yudha; Abd. Qohar; Sisworo (Universitas Teknokrat Indonesia, 2025)
This research applies a qualitative descriptive approach. The purpose of this research is to describe students' problem-solving abilities in solving the PISA test based on each type of learning style, namely visual, auditory, and kinesthetic. The students involved in this research were 35 students, class X from SMA Negeri 1 Kedungwaru, Tulungagung. The method of obtaining data was by using students’ answer sheets and interview results. The results obtained from this research indicate that students carry out Polya steps when solving the PISA test. Based on the characteristics of learning styles, it shows that (1) a student with a visual learning style finds it easier to write than to tell when solving the test and uses previously seen methods, (2) a student with an auditory learning style is good at speaking and able to understand information by listening to explanations from other people, and (3) a student with a kinesthetic learning style is used to practicing directly without being connected to what has previously been seen and heard. Therefore, teachers should pay attention to each type of student learning style to achieve learning goals effectively and well.